Exploring Pre-Service Teachers’ Critical Thinking and Mathematical Beliefs Through Contextual Problem Analysis - Rahaju Rahaju; Tatik Retno Murniasih; Sri Hariyani; Hafis Hafis (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The ability to create contextual problems is essential for pre-service teachers. However, many teachers simply adapt or adopt existing problems when creating contextual problems. This study aims to explore the critical thinking skills in analysing contextual problems and the mathematical beliefs that underlie the analysis process. This qualitative study involved 40 pre-service primary school teacher participants, with four participants selected for in-depth interviews. The research instruments included vignettes, interview guidelines, and observation sheets. The data were validated using triangulation methods. The study indicates that pre-service primary school teachers can be categorised into non-critical thinkers (35 participants), emergent critical thinkers (3 participants), and advanced critical thinkers (2 participants). Non-critical thinkers demonstrate an ability to understand problems that they have previously studied, as their understanding constrained to the formulae and procedures demonstrated by their teachers. Emergent critical thinkers showed the ability to question the problem formulation and evaluate its contextual relevance, although their reasoning remained influenced by teacher authority. Advanced critical thinkers are characterised by a high level of critical thinking aptitude, often attributed to their perception of mathematics as a discipline rooted in logical reasoning.